Critical Success Factors Leading to Meaningful Industry Institution Interaction in the Indian Setting - Jain, P. C. (Journal of Engineering Education Transformations, 1991)
The intended purpose of Technical Education System is to cater to the manpower needs of the potential employers -the industry. Since industry is the ’consumer’ of the ’product’ of this system, the industrial needs should determine the qualities and characteristics of the ’Product’. In view of this, a close collaboration between industry and the technical institution is imperative.